(3GdGbJUGO GdbjGSjs - (3MSjf Ydj(B, (3HNjJs; (3aJM Gddg SMQ(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ(B,s, 2007)
-(3GdebOeI(B:-(3JYQja GdGbJUGO GdbjGSj (B-(3CgOGa GdGbJUGO GdbjGSj (B-(3YdGbI GdGbJUGO GdbjGSj HGdYdhe GdGNQi G daUd GdKGfj GdGfMOGQ GdNWj GdHSjW, (BSimple Linear Regressio(3GdebOeI (B-(3GdaQVjGJ GdNGUI HGdeJZjQ GdYThGFj (B-(3WQjbI GdeQHYGJ GdUZQi,(BOLS -(3GNJjGQ GdaQVjGJ,(BHypothesess
(3HjHdjhZQGajG(B: (3U(B.403(3;GdedGMb U(B.410 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdEbJUGO GdbjGSjs